Potensi Pengembangan Rute di Bandar Udara Mutiara SIS Al Jufri-Palu - Lita Yarlina (Air Transportation Research and Development Center, 2018)
The Development Potential of Air Transportation Routes at Mutiara SIS Al Jufri Airport Palu: The government policy in regulating the air transportation routes on a macro basis aims to open up regional isolation and develop the potential of those regions. Mutiara SIS Al Jufri Airport is one of the entrances to the movement of people and goods through air transport to Central Sulawesi Province. Along with the increasingly socio-economic development of Palu City and Central Sulawesi Province in general, the demand for movement of people and goods also increased, and with the economic improvement of society of Central Sulawesi Province, air transportation becomes the main choice. This study is intended to measure the potential for the development of aviation routes at Mutiara SIS Al Jufri Airport, based on the opinion of current users of air transport and air carrier services, and adapted to the Master Plan of the Airport and the Spatial Planning Document of Central Sulawesi Province, using multiple linier regression analysis method. The results of the survey to the airlines provide the information about the plan to open the Palu-Morowali flight route due to its potential demand for transportation of goods between those cities using ATR-72 type aircraft, where there are many production of mining and palm oil products in Morowali. However, from the analysis, if ATR-72 aircraft should be operated then the runway capacity at Morowali Airport have to be developed since the current condition with runway length of 1,050 m is not sufficient to be landed by ATR-72 in which require a runway with minimum length of 1,600 m.